2018
DOI: 10.1186/s12884-018-1752-y
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating autonomous, confident and satisfying choices: a mixed-method study of women’s choice-making in prenatal screening for common aneuploidies

Abstract: BackgroundPopulation-based prenatal screening has become a common and widely available obstetrical practice in majority of developed countries. Under the patient autonomy principle, women should understand the screening options, be able to take their personal preferences and situations into account, and be encouraged to make autonomous and intentional decisions. The majority of the current research focuses on the prenatal screening uptake rate, women’s choice on screening tests, and the influential factors. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 53 publications
(57 reference statements)
2
13
0
Order By: Relevance
“…Studies conducted in Denmark and Great Britain [ 23 , 24 ] support the idea of mental preparation and the importance of sufficient information, as they found that women had less decisional conflict the better informed they were. A recent study in Finland also supports the importance of informed decision, as women in late pregnancy, with a previous informed decision were more satisfied with their decisions concerning screenings [ 25 ]. Another study found well-informed women to have no more anxiety than their peers [ 24 ], but interestingly in a study by Lalor and Begley [ 19 ], women claimed that it is better not to be too informed beforehand, as extensive information could end up worrying many women for no reason.…”
Section: Discussionmentioning
confidence: 85%
“…Studies conducted in Denmark and Great Britain [ 23 , 24 ] support the idea of mental preparation and the importance of sufficient information, as they found that women had less decisional conflict the better informed they were. A recent study in Finland also supports the importance of informed decision, as women in late pregnancy, with a previous informed decision were more satisfied with their decisions concerning screenings [ 25 ]. Another study found well-informed women to have no more anxiety than their peers [ 24 ], but interestingly in a study by Lalor and Begley [ 19 ], women claimed that it is better not to be too informed beforehand, as extensive information could end up worrying many women for no reason.…”
Section: Discussionmentioning
confidence: 85%
“…A rise in the proportion of cases detected in the first‐trimester would allow termination at an earlier gestational age, which is associated with lower complication rates 27 . An early diagnosis increases reproductive autonomy, but may also shift the time reference for psychological distress 28‐30 . Additionally, early diagnosis potentially improves outcomes for affected individuals by enabling parents and physicians to offer prophylactic initiatives before and after birth to prevent early childhood morbidity 12 …”
Section: Discussionmentioning
confidence: 99%
“…In the decision-making process, women confer a great importance to the technical features of the test, in particular accuracy, safety, timing and easiness (Beulen et al, 2015;Carroll et al, 2013;Chen et al, 2017Chen et al, , 2018Farrell et al, 2014, Lewis et al, 2014Lund et al, 2018;Seror et al, 2019;Skutilova, 2015;van Schendel et al, 2016). Some studies show that the most important factors for choosing NIPT are its high detection rate and the absence of physical risks for the fetus, along with the easiness of the procedure, especially for high-risk women (Chen et al, 2017;Lewis et al, 2016).…”
Section: Test Characteristicsmentioning
confidence: 99%
“…Finally, the gestational age at which the test can be performed is another relevant factor (Chen et al, 2017(Chen et al, , 2018.…”
Section: Test Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation